Corruption and disasters in the built environment: a literature review. Issue 4 (11th July 2022) - Sanderson, David; Patel, Sonny S.; Loosemore, Martin; Sharma, Anshu; Gleason, Kelsey; Patel, Ronak
Abstract : This paper presents the findings of a review of academic literature concerning the degree to which corruption worsens disasters triggered by natural hazards in the built environment. The research employed a 'systematic literature review' methodology to analyse leading academic databases, resulting in a detailed analysis of 59 peer‐reviewed, published papers. It found that while much of the literature focuses on earthquakes (relating to building and infrastructure collapse), the quality of governance, and the drivers of corruption, there is presently very limited scholarship on the general scope, reach, and scale with respect to how disasters are worsened by corruption. It is notable that the Sendai Framework for Disaster Risk Reduction 2015–2030 and a number of other high‐level reports fail to mention corruption. The paper argues that this serious gap in understanding and expressing how corruption increases vulnerability in the built environment within disaster studies perversely supports the furtherance of corruption in worsening disasters نبذة مختصرة: يعرض هذه المقال نتائج مراجعة الأدبيات الأكاديمية المتعلقة بالدرجة التي يؤدي فيها الفساد إلى تفاقم الكوارث الطبيعية في البيئة المبنية. استخدم البحث منهجية "مراجعة منتظمة للأدبيات" لتحليل قواعد البيانات الأكاديمية الرائدة، مما أدى إلى تحليل مفصل لـ 59 بحثًا منشورًا تمت مراجعتهم من قبل الزملاء. لقد وجد أنه في حين أن الكثير من الأدبيات تركز على الزلازل (المتعلقة بالبناء وانهيار البنية التحتية) ونوعية الحوكمة ودوافع الفساد، هناك حاليًا منحة دراسية محدودة فيما يتعلق بالنطاق العام ومدى وكيفية تفاقم الكوارث بسبب الفساد. الكلمات المفتاحية : البيئة المبنية، الفساد، الشفافية 摘要: 本文介绍的学术文献综述是关于腐败在多大程度上加剧了建筑环境中自然引发的灾害。该研究采用"系统文献综述"方法来分析主要的学术数据库，从而对59篇经同行评议已发表论文进行了详细分析。研究发现，虽然大部分文献都集中在地震（关于建筑和基础设施倒塌）、治理质量和腐败的驱动因素上，但目前关于腐败如何使灾害恶化的一般范围、影响和规模的学术研究有限. 关键词：建筑环境，腐败，透明度